Types and names of higher education institutions in the Polish system of higher education and science - Rączka, Piotr; Jędrzejewski, Tomasz (Studia Iuridica Toruniensia, 2023)
Among the basic entities performing tasks within the Polish system of higher education and science, the legislator includes HEIs, which are obliged to perform other tasks related to education. HEIs, with such an extensive system, do not constitute a uniform category; they are an internally diverse group. In order to enable the identification of their scientific potential, which should interact with the teaching potential, the legislator in the Law on Higher Education and Science reserves certain names and makes the use of these names conditional on the fulfilment of statutory criteria. This paper aims to analyse the previous and current legal regulations in this respect and formulate conclusions to further develop the solutions in question.